Bilogical recultivation of post-mining peatlands on the base of energy crops cultivation - Rodzkin, Aleh I.; Charnenok, Evgenija V.; Glukhovskij, Victor I.; Rakovich, Viacheslav A. (Journal of the Belarusian State University. Ecology, 2020)
Thea area of post-mining peatlands in Belarus is 209,5 thousands hectares. These areas belong to degraded lands, and its reclamation is complicated task because of poor fertility and high variability. The goal of our experiments wasassessment of effectivity of biological reclamation of post-mining peatlands on the base of biomass of energy crops obtaining and composite briquette production with adding of peat. Fast growing willow trees were chosen for biologicalreclamation, because they may fustily accumulate biomass (7–10 dry ton per year) on peaty lands with high level of peat decomposition. These rates of biomass accumulation of willow on peaty lands were comparable to willow biomass onmineral soils. The additional source of biomass in the regions which are close to post-mining peatlands is crops residues (straw). The comprehensive assessment of technological characteristics of experimental briquette with different rates ofbiomass (sawdust and straw) and peat have been done. The optimal characteristics have fuel which was produced from sawdust and peat.
Keywords: biological reclamation; biomass; energy crops; composite fuel; briquette